Impact of self-talk among university futsal player in University of Putra Malaysia: a qualitative approach - Jakiwa, Jorrye; Soh, Kim Geok; Omar Fauzee, Mohd Sofian (Minda Masagi Press, 2015)
One of the approaches often used by athletes in order to improve psychological ability is self-talk. Self-talk is the internal language of self. Psychologist states that self-talk can influence factors such as confidence, enthusiasm, diligence, concentration, and strength, as well as reduce anxiety. The purpose of this study was to examine the effects of positive self-talk on performance among futsal players in University of Putra Malaysia. All of the eight respondents were males age between 21–24 (22.13 ± 1.13) years of age, who agreed to participate in this qualitative study. Each of the subject agreed to be interviewed and to have their interview sessions recorded using an audio recorder. For the data interpretation, each of the recording was transcribed and coded by three researchers to determine the main themes of the attributes of self-talk among futsal players. As a result, there are five main themes that were generated from the whole interviews, namely: motivation, focus, effort (hard work), anxiety control, and encouragement. As a conclusion, the main effect of using self-talk among university futsal players is not only to increase motivation, encouragement, and anxiety control, but also to gain the spirit of hard work and improve focusing.